1997
DOI: 10.1074/jbc.272.20.13126
|View full text |Cite
|
Sign up to set email alerts
|

The Substitution of a Single Amino Acid Residue (Ser-116 → Asp) Alters NADP-containing Glucose-Fructose Oxidoreductase ofZymomonas mobilis into a Glucose Dehydrogenase with Dual Coenzyme Specificity

Abstract: Glucose-fructose oxidoreductase (GFOR, EC 1.1.1.99.-) from the Gram-negative bacterium Zymomonas mobilis contains the tightly bound cofactor NADP. Based on the revision of the gfo DNA sequence, the derived GFOR sequence was aligned with enzymes catalyzing reactions with similar substrates. A novel consensus motif (AGKHVXCEKP) for a class of dehydrogenases was detected. From secondary structure analysis the serine-116 residue of GFOR was predicted as part of a Rossmann-type dinucleotide binding fold. An enginee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 47 publications
2
55
0
Order By: Relevance
“…Plasmid pTW43, with point mutations S116D, K121A, K123Q, and I124K in the NADP binding site, was constructed by replacing a 289-bp PstI-SphI fragment of pTW42 with the respective fragment of plasmid pZY470/S116D/K121A/ K123Q/I124K (45).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasmid pTW43, with point mutations S116D, K121A, K123Q, and I124K in the NADP binding site, was constructed by replacing a 289-bp PstI-SphI fragment of pTW42 with the respective fragment of plasmid pZY470/S116D/K121A/ K123Q/I124K (45).…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we have described various mutant derivatives of the GFOR protein which contain an alteration in one or more amino acid residues located in the NADP-binding Rossman fold and which are impaired in tight binding of the NADP cofactor (45). In addition, we demonstrated that these GFOR mutant proteins with reduced affinity for NADP lost the ability to oxidize glucose and reduce fructose but instead were able to exchange reduced cofactor (NADPH) for the oxidized form (NADP), therefore acting as glucose dehydrogenases (45). Since these mutant forms of GFOR still exhibit enzymatic activity, the overall three-dimensional structure should be intact.…”
Section: Vol 183 2001mentioning
confidence: 99%
“…The highest similarity was found to be to a group of dehydrogenases containing the consensus motif AGKHVXCEKP, all of which are known to, or can be expected to, react with substrates that are structurally similar to glucose (24). The deduced product of thuA is a protein of unknown function with an amidotransferase motif.…”
mentioning
confidence: 96%
“…Site-directed mutagenesis and X-ray crystallographic studies [46,47] have revealed that this enzyme has a typical dinucleotide-binding domain, i.e. a Rossmann (β-α-β) fold [48] with a fingerprint sequence, an N-terminal Gly-Xaa-Gly-Xaa-Xaa-Ala sequence and a Glu-Lys-Pro motif for interaction with the carboxamide group of the nicotinamide ring and the nicotinamide ribose.…”
Section: Alignment Of Dimeric Dds With Other Proteinsmentioning
confidence: 99%
“…As described above, chemical modification [45] and our site-directed mutagenesis studies suggest that His-79 is important in catalysis or substrate binding in dimeric DD. Thus GFO and dimeric DD might be distinct with respect to their catalytic residues, because the subunit structures and catalytic properties of the two enzymes are different : GFO is tetrameric and catalyses a Ping Pong type of reaction in the oxidoreduction of glucose and fructose through the tightly bound coenzyme [46], whereas dimeric DD is a simple dehydrogenase that follows an ordered Bi Bi mechanism [51]. In the proposed medium-chain dehydrogenase\reductase family (Figure 2), several residues other than His-79, the Glu-Lys-Pro motif and Tyr-180 are strictly conserved ; these are targets of a future site-directed mutagenesis study to understand further the structural and evolutionary relationship between the members of this family and related proteins, including GFO.…”
Section: Alignment Of Dimeric Dds With Other Proteinsmentioning
confidence: 99%